Eye Contact in Video Communication: Experiences of Co-creating Relationships - Kaiser, Niclas; Henry, Kimberly; Eyjólfsdóttir, Hanna (Frontiers in Psychology, 2022)
As a result of the COVID-19 pandemic, increased number of persons have been forced to limit their interactions with friends and families to contact via video, which excludes eye-contact. The aim of this study was to examine individuals’ experiences of the difference between forced skewed visuality and the ability for eye-contact in conversations. Two custom-made units allowed 15 participants interacting in dyads to alternate between being able to make eye contact and having that ability removed through skewed visuality. Participants reported their experiences in semi-structured interviews. Data analyzed with qualitative content analysis resulted in three themes: Shared eye contact allows us to create our relationship together; With eye contact, we adjust to each other to feel more connected and less intimidated; and We get more self-conscious when the visuality is skewed or shifting. The results imply that skewed visuality as forced lack of eye-contact in video conversations effects embodied non-verbal processes related to sense of connectedness and participatory sensemaking, creating a sense of both emotional and physical distance, as well as heightening self-awareness about the need of actively regulating the other. We argue that this is one of the ways to understand the impact of moving interactions to online communication.